2023
DOI: 10.18280/ijsdp.180333
|View full text |Cite
|
Sign up to set email alerts
|

Income Diversity and Other Socioeconomic Factors That Influence the Household Food Security of Small-Scale Lowland Rice Farmers in Indonesia

Abstract: Farmers face many challenges, such as decreased agricultural productivity and decreased household income, which impact farmers' food insecurity. This study aims to analyze the effect of income diversity and other socioeconomic factors on the household food security of smallscale lowland rice farmers. This study uses multivariate logistic regression and input from 264 lowland rice families to explain the relationship between income diversification and other socioeconomic factors on household food insecurity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…It is well-established that rural households typically exhibit higher levels of food insecurity compared to their urban counterparts (Amrullah et al, 2019;Grimaccia & Naccarato, 2019). Agricultural workers engaged in small-scale enterprises often contend with low incomes, predisposing them to food insecurity (Antara et al, 2023). Concerning the factor of age, older individuals in regions characterized by higher income levels tend to face comparatively lower food security, whereas in areas with lower income levels, age differentials do not significantly influence food security status (Omidvar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-established that rural households typically exhibit higher levels of food insecurity compared to their urban counterparts (Amrullah et al, 2019;Grimaccia & Naccarato, 2019). Agricultural workers engaged in small-scale enterprises often contend with low incomes, predisposing them to food insecurity (Antara et al, 2023). Concerning the factor of age, older individuals in regions characterized by higher income levels tend to face comparatively lower food security, whereas in areas with lower income levels, age differentials do not significantly influence food security status (Omidvar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that various factors are crucial in determining household food security, including the geographic location of the household (Ali et al, 2016;Ganpule et al, 2023), type of occupation (Antara et al, 2023;Ogundari, 2017), age and gender of the head of the household (Ogundari, 2017;Omidvar et al, 2019), their education level (Amrullah et al, 2019;Smith et al, 2017), family size (Lujabe et al, 2022), marital status (Grimaccia & Naccarato, 2019), and ownership of assets such as houses (Pakravan-Charvadeh et al, 2022;Saint Ville A et al, 2022), land (Naipunu & Kadir, 2023), and social security (Sutikno & Budiasih, 2022). Utilizing these factors in the analysis of regional-level data is essential for a better understanding of food security statistics at the regional level in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…A nivel de los hogares, los aspectos más relacionados con la inseguridad alimentaria son el ingreso mensual (Antriyandarti et al, 2023;Yazew et al, 2023;Rezaul Karim & Tasnim, 2022) y el tamaño del hogar (Yazew et al, 2023, Adeoye et al, 2022& Pakravan-Charvadeh et al, 2022. Otros factores que también están ligados, son el número de trabajadores familiares, la experiencia agrícola, el tamaño de la finca y la producción (Antriyandarti et al, 2023), la diversificación de los ingresos del jefe de hogar (Antara et al, 2023), la diversidad dietética (Yazew et al, 2023), mujeres que ganen menos que el salario mensual básico, jefes de hogar sin pareja matrimonial, hogares que no reciben apoyo económico (Adeoye et al, 2022), la salud debilitada de los niños (Varela et al, 2022), hogares con niños en edad escolar, hogares encabezados por mujeres (Pakravan-Charvadeh et al, 2022), ocupación materna como ama de casa, pérdidas de empleo (Rezaul Karim & Tasnim, 2022), niños en edad preescolar y escolar con padres con educación baja y media (Silva et al,2022). Hoy en día, mejorar el estado de seguridad alimentaria sostenible, es un desafío importante a nivel mundial, principalmente en los países en vías de desarrollo (Pakravan-Charvadeh et al, 2022).…”
Section: Introductionunclassified